P. K. Srivastava. Marketing Management in a Developing Economy. New Delhi: Sterling Publishers. 1991. vi + 559 pp.Price: Indian Rs 300.00 (The Pakistan Development Review, 1991)
Marketing management is an important topic for those projects that depend on maximizing the sale of their output, especially in the industrial and agricultural sectors of the developing countries. This, however, does not mean that marketing management is only applicable to the directly productive/extractive sectors of the economy. Increasingly, with the passage of time, the service sector in both the developed and the developing countries has also expanded dramatically (pakistan's fastest growing sector is the service sector). Here, also, marketing management can play an important role. Five discrete steps can be singled out when a project is to be established; namely, identification, preparation, appraisal, implementation, and evaluation. This whole process is called the 'project cycle', and all projects, irrespective of the sector of the economy in which they are being established, have to follow in a sequential order the different stages outlined at the beginning of this paragraph. At the same time, it should be pointed out that, in the present-day world, project preparation and appraisal, in particular, have become very interdisciplinary in nature. Thus, it would be no surprise to have economists, anthropologists, demographers, marketing specialists, and engineers all working together in the design and implementation of projects. Further, it need not be over-emphasized that proper project identification and execution helps to propel the growth rate upwards, raising the living standards and improving the general economic well-being, which are the stuff of development.